2018
DOI: 10.1111/jcpe.13008
|View full text |Cite
|
Sign up to set email alerts
|

Third molars and periodontal damage of second molars in the general population

Abstract: In particular, in the mandible, those findings could guide dental practitioners more in the direction to remove the third molars after having evaluated the periodontium of the adjacent teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…In this context, studies have confirmed that the presence of impacted M3s (I-M3s) increases the risk of M2 pathology by 1.45-4.88 folds [8,9]. In recent years, investigations have found that erupted M3s (E-M3s) also negatively impact oral health and scientists have reported that the presence of E-M3s increases the risk of M2 pathology by 1.44-1.77 folds [8,9,10]. When M2s are too heavily damaged to be treated or controlled, they can only be removed.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this context, studies have confirmed that the presence of impacted M3s (I-M3s) increases the risk of M2 pathology by 1.45-4.88 folds [8,9]. In recent years, investigations have found that erupted M3s (E-M3s) also negatively impact oral health and scientists have reported that the presence of E-M3s increases the risk of M2 pathology by 1.44-1.77 folds [8,9,10]. When M2s are too heavily damaged to be treated or controlled, they can only be removed.…”
Section: Introductionmentioning
confidence: 97%
“…[6]. Among the various risk factors to M2 pathology, the presence of its neighboring M3s has attracted increasing attention [7,8,9]. In this context, studies have confirmed that the presence of impacted M3s (I-M3s) increases the risk of M2 pathology by 1.45-4.88 folds [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different types of M3s, it is generally believed that impacted third molars (I‐M3s) are often symptomatic and have an increased likelihood to be a risk factor for disease development in neighboring teeth (Polat, Ozan, Kara, Ozdemir, & Ay, 2008; Yilmaz, Adisen, Misirlioglu, & Yorubulut, 2016). However, recent investigations have found that retained non‐impacted third molars (N‐M3s), that is, erupted M3s, also negatively impact dental health (Kindler et al, 2018; Li, Qu, Zhou, Tian, & Chen, 2017; Li, Qu, Zhou, Tian, Gao, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were also found in the general population. Among the total population, subjects with mandibular erupted third molars (most likely N‐M3s) had a higher risk of deep PD values in their adjacent M2s than those without M3s (Kindler et al, 2018). On the other hand, a cross‐sectional study based on radiological data of 4,057 patients showed that the prevalence of alveolar bone loss in the distal M2s adjacent to N‐M3s was 40.4%, which was similar to that of M2s adjacent to I‐M3s (41.5%; Li, Qu, Zhou, Tian, & Chen, 2017).…”
Section: Introductionmentioning
confidence: 99%